Development of a dried blood spot sampling method towards therapeutic monitoring of radotinib in the treatment of chronic myeloid leukaemia. - Lee, Jihyun; Jung, Su Young; Choi, Mi‐Yeon; Park, Ji‐su; Park, Su‐kyoung; Lim, Seon‐Ah; Cho, Kyung Hee; Oh, Soo Yeon; Ha, Jungeun; Kim, Dong‐Wook; Lee, Jangik (Journal of Clinical Pharmacy & Therapeutics, 2020)
What is known and objective: Dried blood spot (DBS) sampling is a minimally invasive method of blood sampling that enables monitoring of drug concentrations to be more convenient. This study aimed at developing a DBS sampling method for an accurate and precise prediction of radotinib plasma concentrations (Cp) in patients with chronic myeloid leukaemia (CML). Methods: Dried blood spot and venous blood samples were simultaneously collected from fifty CML patients who had been receiving radotinib for at least a week. Radotinib concentrations were measured using a high‐performance liquid chromatographic method with tandem mass spectrometric detection. Unmeasured Cp was predicted directly based on a Deming regression between DBS concentrations (CDBS) and Cp. Unmeasured Cp was also predicted from CDBS corrected by each patient's haematocrit (Hct). Both prediction methods were evaluated for their accuracy and precision using Deming regression and Bland‐Altman analysis. Results and discussion: The Deming regression equation between CDBS and Cp was obtained as follows: Cp = 1.34∙CDBS + 4.26 (r2 =.97). Cp was directly predictable using Cp,pred1 = 1.34∙CDBS + 4.26. With Hct correction, Cp was alternatively predictable using Cp,pred2 = CDBS/ (1–Hct + Hct2). The slopes of Deming regression line between predicted and measured Cp were 0.99 and 1.02 for the direct and Hct‐corrected method, respectively. The mean biases (accuracy) were −0.44% and 1.6% with the 95% limits of agreement (precision) of −22.4% to 21.5% and −20.5% to 23.7%, respectively. More than 93% of predicted and measured Cp pairs had their differences within 20% of the mean of each pair in both methods. What is new and conclusions: Radotinib CDBS are highly correlated with radotinib Cp. Radotinib Cp can be accurately and precisely predicted from CDBS using direct or Hct‐corrected prediction methods. Both appear to be appropriate for the therapeutic monitoring of radotinib in patients with CML.